2022
DOI: 10.1121/10.0009845
|View full text |Cite
|
Sign up to set email alerts
|

Is jet fuel exposure associated with central auditory nervous system difficulties: An exploratory study in military personnel

Abstract: Central auditory nervous system dysfunction (CANSD) can manifest as hearing difficulty in the absence of audiometric abnormalities. Effects of noise or jet fuel exposure on the CANS are documented in animal models and humans. This study screened military personnel using the modified Amsterdam Inventory for Auditory Disability (mAIAD) to assess whether concurrent jet fuel and noise (JFN) exposures potentiate central auditory difficulties compared to noise only exposures. A total of 48 age- and sex-matched parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…In the current study, the (m)AIADH showed discriminative ability between the group with good perceived hearing and the group with bad perceived hearing. This corroborates the Dreisbach et al 25 study that revealed participants with more listening difficulty demonstrated worse (m)AIADH scores. Another study conducted by Fuente et al 26 also reported similar findings, which showed a solvent‐exposed group had poorer hearing than the nonexposed and the (m)AIADH was able to differentiate those two groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the (m)AIADH showed discriminative ability between the group with good perceived hearing and the group with bad perceived hearing. This corroborates the Dreisbach et al 25 study that revealed participants with more listening difficulty demonstrated worse (m)AIADH scores. Another study conducted by Fuente et al 26 also reported similar findings, which showed a solvent‐exposed group had poorer hearing than the nonexposed and the (m)AIADH was able to differentiate those two groups.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the (m)AIADH showed discriminative ability between the group with good perceived hearing and the group with bad perceived hearing. This corroborates the Dreisbach et al 25 This study also demonstrated satisfactory convergent and criterion validity of the (m)AIADH. The worse the firefighters perceived their hearing level, the higher the scores of (m)AIADH.…”
Section: Criterion Validitysupporting
confidence: 91%
“…In addition, the authors determined the AIADH scores were significantly associated with pure-tone thresholds and RGD results. A recent study by Dreisbach et al 49 reported consistent and marked lower scores of a modified AIADH version for a group of military personnel exposed to jet-fuels, when compared to a control group.…”
Section: Discussionmentioning
confidence: 89%